2011
DOI: 10.1002/14651858.cd008063.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing for substance abuse

Abstract: Co-registration This review is co-registered within both the Cochrane and Campbell Collaborations. A version of this review can also be found in the Cochrane Library. Keywords Contributions Karlsen conceived of the idea and commissioned the review. All reviewers were involved in planning the review. Smedslund wrote the methods section of the protocol. Karlsen and Smedslund wrote the background. Hammerstrøm developed the search strategy, performed the original searches and the final search in November 2010. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
179
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(201 citation statements)
references
References 238 publications
3
179
1
8
Order By: Relevance
“…Moreover, the effect size from every meta‐analysis in this review favors MI, 19 of 34 (56%) effect sizes demonstrate statistically significant effects, and no studies reported harms for the intervention (see ‘Comparison 1’ in the review). Given the above, we were surprised by the review's strong conclusions unfavorable to MI, especially as the review authors noted that their conclusions differed from another Cochrane review on MI for drug use, even though the other review had similar effect sizes 41. Discrepancies in interpreting similar effect sizes for similar interventions indicate that MCIDs are not defined uniformly in this area, and the review authors’ conclusions represent a particular interpretation of effects (rather than the effects themselves) that differs from other review authors’ interpretations 1, 14, 15.…”
Section: Sustainability and Clinical Significance Of Intervention Effmentioning
confidence: 93%
“…Moreover, the effect size from every meta‐analysis in this review favors MI, 19 of 34 (56%) effect sizes demonstrate statistically significant effects, and no studies reported harms for the intervention (see ‘Comparison 1’ in the review). Given the above, we were surprised by the review's strong conclusions unfavorable to MI, especially as the review authors noted that their conclusions differed from another Cochrane review on MI for drug use, even though the other review had similar effect sizes 41. Discrepancies in interpreting similar effect sizes for similar interventions indicate that MCIDs are not defined uniformly in this area, and the review authors’ conclusions represent a particular interpretation of effects (rather than the effects themselves) that differs from other review authors’ interpretations 1, 14, 15.…”
Section: Sustainability and Clinical Significance Of Intervention Effmentioning
confidence: 93%
“…However, when the evidence for motivational interviewing is taken together, the results are somewhat mixed. For example, there are concerns about the staying power of motivational interviewing interventions, as effect sizes tend to diminish over time (Smedslund et al, 2011).…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…Dentro de las estrategias terapéuticas conductuales se encuentran la realización de terapias cognitivoconductual, entrevistas de motivación y terapias grupales (NIDA, 2008(NIDA, , 2010Engle, 2011;Smedslund et al, 2011).…”
Section: Estrategias Terapéuticasunclassified
“…El consejero tiene un rol activo guiando al sujeto en objetivos a corto y largo plazo y evaluando constantemente su acción sobre estos (Engle, 2011;Smedslund et al, 2011). Adicionalmente, el consejero debe desarrollar empatía con el sujeto para comprender su punto de vista y llevarlo a que perciba la discrepancia entre lo que se es y lo que se quiere ser.…”
Section: Estrategias Terapéuticasunclassified
See 1 more Smart Citation